Biological cell derived N-doped hollow porous carbon microspheres for lithium–sulfur batteries. Issue 40 (23rd September 2016) - Xie, Yanping; Fang, Liang; Cheng, Hongwei; Hu, Chenji; Zhao, Hongbin; Xu, Jiaqiang; Fang, Jianhui; Lu, Xionggang; Zhang, Jiujun
Abstract : A green self-templating approach was designed to fabricate N-doped hollow porous carbon microspheres (NHPCMs) through renewable yeast cells for encapsulating sulfur. Abstract : Lithium–sulfur (Li–S) batteries are appealing for next generation efficient energy power systems due to their high energy density and low cost. Yeast cells, as a natural biotemplate, are self-duplicable, nitrogen-rich, inexpensive and regular in morphology. Yeast cells show promising applications in the synthesis of nitrogen-doped hollow porous carbon materials for energy storage and transition systems. In this work, we have developed a green and facile self-templating route through low-cost and renewable yeast cells with hollow structures to fabricate N-doped hollow porous carbon microspheres (NHPCMs) for encapsulating sulfur. The sulfur-loaded NHPCM (NHPCM@S) composite with 65 wt% sulfur is then used as the cathode material for Li–S batteries. These batteries exhibit a reversible specific capacity of 1202 mA h g −1 and a capacity retention of 725 mA h g −1 over 400 cycles at 0.1C with a capacity decay of 0.09% per cycle, as well as an enhanced rate performance of 587 mA h g −1 at 2C. In the NHPCM@S composite, the stable micro/mesoporous carbon shell acts as an efficient reservoir for soluble polysulfide, and the doped nitrogen in the carbon shell can offer exceptional electronic conductivity and strong adsorption for polysulfide species. This work demonstrates that an environmentally friendly, economical, sustainable, and self-templating route for N-doped hollow porous microspheres with natural and reproducible biological resources can lead to exciting developments in Li–S batteries and their practical applications in portable electronic devices, advanced electric vehicles, and energy storage systems.